VARIOUS ECOLOGICAL IN THE CIRCUMSTANCES LIVING SCHOOL OF ARCHERS PHYSICAL ABILITY TO WORK AND HEMODYNAMIC PARAMETERS - G.N. Ernazarov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
PWC 170 test was used to determine students’ physical work ability. Anfilov’s correction chart was used to monitor mental performance. Changes in hemodynamic indicators were determined for the physiological classification of the effects of physical activity.